Concepts and Approaches for Delineating the Rural Urban Fringe - Kumar, Chandan; Sinha, B.R.K. (National Geographical Journal of India, 2022)
The rural-urban fringe area is a dynamic spatial zone caused by the effect of the process of urbanization at the outer limit of the city, i.e. beyond the municipal or any other administrative boundary of a city. This occupies an important place in the field of urban geography, because it forms a complex identity of physical spreadness and social, cultural, economic and environmental transforming conditions over a period of time. The rural-urban fringe area stands for the spatial extension between a city and a countryside. Looking into the complex web of transformation, the delineation of rural-urban fringe area becomes very important. However, to determine the concepts and approaches for delineating the boundary between the urban and rural segments is a difficult task for a researcher. In the light of the above facts, this paper aims at developing the conceptual frame of the concepts and approaches to be employed in delineating the rural-urban fringe area. This paper is based on the previous works carried out by several urban experts at national and international level. Therefore, this paper deals with bases concerning appropriate variables or parameters to be used in delineating the rural-urban fringe zone. For this, there is a need for determining, and selecting appropriately useful indicators or variables to apply in delineating a rural-urban fringe area in context of any city of the world.